Multidisciplinary Approaches in Surgical Treatment and Rehabilitation of Patients with Defects of Trachea Anterior Wall - Rustem Hayaliev1, Shukhrat Khudaybergenov2, Otabek Eshonkhodjaev3, Abdurashit Kayumhodjaev4, Nazira (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Elimination of persistent and extensive defects of the anterior wall of the trachea is one ofthe urgent problems and continues to be the subjects of researches and discussions of the thoracic surgeons,plastic surgeons and otolaryngologists. The authors presented the results of treatment of 118 patients withextensive defects of trachea in subglottic division of the larynx and soft tissues of the neck after laryngotracheostomyor tracheostomy.Materials and Method: The authors consider that the choice of the method of plastic surgery or reconstructionof the tracheal defect is determined individually in each case. If the size of the defect of the trachea is upto 2x4 cm, the sufficient depth of the trachea lumen corresponds to the lumen above and below the stoma,the common axis of the trachea and the distal part of the larynx are without displacement and deformationof the lumen, then a skin-muscle plasty of the defect with the substitution of local tissues is recommended.Results: Local three-layer or four-layer skin-muscle plastic operations were performed in patients withdefect sizes from 1.0 sm to 2.0 sm wide and from 2.0 sm to 4.0 sm long, with a defect depth of more than8 mm, i.e. anterior-posterior size of the tracheal lumen and a stable formed lumen of the respiratory tract inthe zone of plastic contraction without the presence of a protector (T-shaped stent or tracheostomy cannula).Eleven patients with extensive defects of the anterior-lateral walls of the trachea and distal larynx underwentcomplex reconstructive operations using microsurgical techniques.Conclusion: The use of displaced flaps allows: to form a mucous membrane in the defect area withouttension of the lateral walls of the trachea (the first layer); to close the defect (or to cover the cartilaginousimplant) with a well blood-supplied second flap. A complex-compound prefabricated flap (Delta-pectoralskin-fascial-cartilaginous flap) can be used in the presence of a persistent defect and formed tracheal lumenat this level, without signs of restenosis of the respiratory tract, in the absence of inflammation and infectionof tissues around the defect. The skin-muscle-bone revascularized complexes of auto-tissues correspond allthe requirements of tracheal surgery, allowing to reduce the risk of infectious and trophic complications.